2022
DOI: 10.3390/plants11070955
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen–Salt Interaction Adjusts Root Development and Ion Accumulation of the Halophyte Suaeda salsa

Abstract: Nitrogen (N) application might exert a great impact on root (biomass, length) distribution, which possibly contributes to ion and nutrient uptakes. Here, we address the effects of N application on these characteristics to detect how N improves its salt tolerance. Suaeda salsa was subjected to four salt levels (0.5, 1.0, 1.5, and 2.0%) and three N treatments (NO3−-N: 0, 0.25, and 0.50 g·kg−1) in soil column experiments. The N applications performed a “dose effect” that significantly enhanced the growth of Suaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…S. salsa and Z. mays L. are two kinds of highly nitrogen-demanding plants, and insufficient nitrogen adversely affects their growth [ 20 , 21 ]. It was not to be ignored that, as the most direct exposure to adversity, root structure and function are terribly important to enhance the uptake in soil nutrients and accelerate microbial activities [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…S. salsa and Z. mays L. are two kinds of highly nitrogen-demanding plants, and insufficient nitrogen adversely affects their growth [ 20 , 21 ]. It was not to be ignored that, as the most direct exposure to adversity, root structure and function are terribly important to enhance the uptake in soil nutrients and accelerate microbial activities [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is an important regulatory factor that acts on halophytes at different developmental stages in their life history [ 20 , 21 ]. Studies have shown that the NO 3 − -N application can promote the germination and vigor index of suaeda seeds [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations